ACCURACY OF THE SOIL SEALING ENHANCEMENT PRODUCT FOR POLAND - Krówczyńska, Małgorzata; Soszyńska, Agnieszka; Pabjanek, Piotr; Wilk, Ewa; Hurbanek, Pavol; Rosina, Konstantin (Quaestiones Geographicae, 2016)
Increasing urbanization results in constant enlarging of the artificial area closed to water infiltration. In 2006–2008, the Soil Sealing Enhancement (SSE) database was the part of the GMES Fast Track Service on Land Monitoring. The accuracy of the final product set by the authors should reach at least 85%. Orthorectified high resolution aerial photos of Poland were used to develop reference data constituting 20,000 random samples around the country. In each sample, the points were classified into three possible surface classes: natural, artificial and semi-sealed. Comparison of reference data to original project statistics revealed the values of accuracy, commission and omission errors in the SSE dataset. Although, SSE accuracy in Poland fulfils the criteria set by SSE authors with overall accuracy of 99.5%, the individual analysis for each category reveals many weaknesses. Preliminary interpretation of mistakes leads to the conclusion that the spatial resolution of pictures used in the SSE project is insufficient. In several cases, validation proved that omission errors were made in relation to construction sites or recently constructed buildings. It should be stated that the accuracy of SSE product for Poland should be treated as the maximum value of impervious surfaces.